Pengaruh Brain Gym terhadap Fungsi Kognitif pada Lansia di Panti Werdha Majapahit Kabupaten Mojokerto - Maria Suci Lestari; Lilik Ma'rifatul Azizah; Etik Khusniyati (Akademi Kesehatan Rustida, 2020)
One health problem that often arises in the old population is a decline in cognitive function. Efforts to improve cognitive function in the old are brain exercises. Brain gym with edu K exercises or training and kinesis (movement) throughout the brain through renewal of certain motion patterns to open previously obstructed or closed parts of the brain. The purpose of this study was to determine the effect of brain gymnastics on improving cognitive function of old. The design used in this research is experimental pra experimental type with pretest-post test one group design approach. The population in this study were all old people who decreased cognitive function in the Majapahit Nursing Home Mojokerto District in July 2018 as many as 22 people. The sampling technique of this research is purposive sampling. The sample size were 13 persons. Independent variable was brain gym while the cognitive function as dependent variable. The instrument used is MMSE questionnaire and brain gymnast SOP. Data analysis using Wilcoxon Test. The results showed that almost all respondents experienced a probable cognitive impairment before doing brain gym in a number of 11 people (86%), and most respondents experienced probable cognitive impairment after a brain gym of 7 people (53.8%). Wilcoxon signed rank test results interpreted ρ value = 0.046<α, so H1 accepted, meaning there was a weak influence of brain gymnastics on old cognitive function in the Majapahit Nursing Home. Movement of brain gymnastics will stimulate parts of the brain to regenerate the brain functions that have decreased, because with brain gymnastics then the blood flow to the brain will be more fluent and meet the needs of brain cells to function properly.